EVALUATING THE IMPACT OF OIL PRICES AND GDP ON IBS LABOUR WAGES AND DEVELOPING A REGRESSION MODEL - JASBIR SINGH, ARVINDERPAL SINGH GILL (Universiti Teknologi PETRONAS, 2021)
Construction labourers are one of the most important pillars in Malaysia's construction sector for project completion.